(untitled) (Global Journal of Human-Social Science, 2022)
This article will to answer the question Why Russia allow a military intervention in the Ukraine on the side of the Russian forces How are we to think of it How are we those that love Russia and especially cherish its peaceful and peacemaking nature going to deal with this situation morally politically A main reason for this war is in fact insufficient representation of the Russian point of view and integration of Russia by Westerns counterparts in the global order despite Russia making all efforts to join it in the last 25 years How are we to maintain the open dialogue and improve the representation of Russia after and during this military conflict The other reason for the conflict is the astounding deafness and unwillingness to compromise or simply acknowledge the Russian position and truth